85.2k views
5 votes
Given the 2 functions find (f+g)(X)

Given the 2 functions find (f+g)(X)-example-1

1 Answer

4 votes

Answer:

f(x) + g(x) = -9x³ - 14x² + 2x + 7

Explanation:

This notation (f + g)(x) just wants you to add the two functions; it's the same thing as writing f(x) + g(x).

f(x) = -6x² + 9x + 7

g(x) = -9x³ - 8x² - 7x

All you have to do now is combine like terms and simplify.

f(x) + g(x) = (-6x² + 9x + 7) + (-9x³ - 8x² - 7x)

f(x) + g(x) = -6x² + 9x + 7 + -9x³ - 8x² - 7x

f(x) + g(x) = -9x³ - 8x² - 6x² + 9x - 7x + 7

f(x) + g(x) = -9x³ - 14x² + 2x + 7

User Ericjbasti
by
5.0k points